The impact of Arctic sea ice loss on mid-Holocene climate - Hyo-Seok Park (Nature Portfolio, 2018)
Mid-Holocene climate was characterized by strong summer solar heating that decreased Arctic sea ice cover. Here the authors show that this sea ice loss had profound effects on the climate system, distinct from direct effects of solar heating, over North America, northern Asia, and the North Atlantic.